2015
DOI: 10.1038/nrurol.2015.29
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial perspectives on sexual recovery after prostate cancer treatment

Abstract: Many therapies for erectile dysfunction (ED) after prostate cancer treatment improve erectile firmness, yet, most couples stop using aids within 1-2 years. Patients and partners who expect immediate and complete success with their first ED treatment can be demoralized when they experience treatment failure, which contributes to reticence to explore other ED aids. Comprehensive patient education should improve sustainability and satisfaction with ED treatments. Pre-emptive and realistic information should be pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 125 publications
(190 reference statements)
1
38
0
2
Order By: Relevance
“…As such, healthcare professionals should be aware that the failure of men to initiate discussions about sexual performance and practices does not mean that they necessarily lack questions or concerns in that area. Moreover, given the diversity of sexual experience and experimentation reported by respondents in our study, an erection-focused prescription for a phosphodiesterase type 5 inhibitors may simply fail to address the patient's broader needs, when they present with ED as a primary complaint (see Dowsett, 2008;Walker et al, 2015). Men with ED are often left on their own to find alternative ways to be sexual that are not erection-dependent.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As such, healthcare professionals should be aware that the failure of men to initiate discussions about sexual performance and practices does not mean that they necessarily lack questions or concerns in that area. Moreover, given the diversity of sexual experience and experimentation reported by respondents in our study, an erection-focused prescription for a phosphodiesterase type 5 inhibitors may simply fail to address the patient's broader needs, when they present with ED as a primary complaint (see Dowsett, 2008;Walker et al, 2015). Men with ED are often left on their own to find alternative ways to be sexual that are not erection-dependent.…”
Section: Discussionmentioning
confidence: 94%
“…Walker et al (2015) have recently suggested that clinicians working with PCa patients should encourage the men to explore non erection-dependent sexual practices concurrently with ED treatments, rather than ignore or introduce these practices as options of last resort. Our findings endorse that perspective.…”
Section: Discussionmentioning
confidence: 99%
“…7 When all ED approaches fail, if penetrative sex is a high priority, discussion about use of an external penile prosthesis may be of interest. 8 However, it is also important to…”
Section: A Complex Issuementioning
confidence: 99%
“…Patients often do not spontaneously note problems with their sex life and prefer health care providers to initiate the discussion because of embarrassment, fear, or other reasons. 8 However, health care providers often feel ill-equipped to deal with sexual health issues, are embarrassed themselves, and often lack resources to offer patients and their partners if they do identify a problem. A recent review provides interested clinicians with insight and in-depth guidance on how to promote sexual recovery after treatment of prostate cancer, advice that can reasonably be applied to those with ED related to treatment for any malignancy.…”
Section: A Complex Issuementioning
confidence: 99%
See 1 more Smart Citation